Team dynamics in a COVID-19 intensive care unit: A qualitative study. Issue 1 (January 2023) - Costa, Deena K.; Wright, Nathan C.; Hashem, Osama; Posa, Antonio M.; Juno, Julie; Brown, Sarah; Blank, Ross; McSparron, Jakob I.
Abstract: Background: During the COVID-19 pandemic, new intensive care units (ICUs) were created and clinicians were assigned or volunteered to work in these ICUs. These new ICU teams were newly formed and may have had varying practice styles which could affect team dynamics. The purpose of our qualitative descriptive study was to explore clinician perceptions of team dynamics in this newly formed ICU and specifically understand the challenges and potential improvements in this environment to guide future planning and preparedness in ICUs. Methods: We conducted 14 semistructured one-on-one interviews with six nurses and eight physicians from a newly formed 36- to 50-bed medical ICU designed for COVID-19 patients in a teaching hospital. We purposively sampled and recruited ICU nurses, medical/surgical nurses, fellows, and attending physicians (with pulmonary/critical care and anaesthesia training) to participate. Participants were asked about team dynamics in the ICU, its challenges, and potential solutions. We then used a rapid analytic approach by first deductively categorising interview data into themes, based on our interview guide, to create a unique data summary for each interview. Then, these data were transferred to a matrix to compare data across all interviews and inductively analysed these data to provide deeper insights into team dynamics in ICUs. Results: We identified two themes that impacted team dynamics positively (facilitator) and negatively (barrier): interpersonal factors (individual character traits and interactions among clinicians) and structural factors (unit-level factors affecting workflow, organisation, and administration). Clinicians had several suggestions to improve team dynamics (e.g., scheduling to ensure clinicians familiar with one another worked together, standardisation of care processes across teams, and disciplines). Conclusions: In a newly formed COVID ICU, interpersonal factors and structural factors impacted the team's ability to work together. Considering team dynamics during ICU reorganisation is crucial and requires thoughtful attention to interpersonal and structural factors.